MAGEB2-Mediated Degradation of EGR1 Regulates the Proliferation and Apoptosis of Human Spermatogonial Stem Cell Lines - Xueheng Zhao; Zenghui Huang; Yongzhe Chen; Qianyin Zhou; Fang Zhu; Huan Zhang; Dai Zhou (Stem Cells International)
Spermatogonial stem cells are committed to initiating and maintaining male spermatogenesis, which is the foundation of male fertility. Understanding the mechanisms underlying SSC fate decisions is critical for controlling spermatogenesis and male fertility. However, the key molecules and mechanisms responsible for regulating human SSC development are not clearly understood. Here, we analyzed normal human testis single-cell sequencing data from the GEO dataset (GSE149512 and GSE112013). Melanoma antigen gene B2 (MAGEB2) was found to be predominantly expressed in human SSCs and further validated by immunohistology. Overexpression of MAGEB2 in SSC lines severely weakened cell proliferation and promoted apoptosis. Further, using protein interaction prediction, molecular docking, and immunoprecipitation, we found that MAGEB2 interacted with early growth response protein 1 (EGR1) in SSC lines. Reexpression of EGR1 in MAGEB2 overexpression cells partially rescued decreased cell proliferation. Furthermore, MAGEB2 was shown to be downregulated in specific NOA patients, implying that abnormal expression of MAGEB2 may impair spermatogenesis and male fertility. Our results offer new insights into the functional and regulatory mechanisms in MAGEB2-mediated human SSC line proliferation and apoptosis.